Great souls six who changed the century - Aikman, David (Nashville Word Pub, 1998)
As a senior journalist with Time magazine, David Aikman witnessed some of the most important world events and interviewed many of the prominent global power figures of his time. In this moving volume, Aikman profiles six of these figures: Billy Graham, Nelson Mandela, Aleksandr Solzhenitsyn, Mother Teresa, Pope John Paul II, and Elie Wiesel. He explains how each of these luminaries personify specific virtues that are sorely needed today: salvation, forgiveness, truth, compassion, human dignity, and remembrance. Aikman's meticulous research provides extraordinary insights into the lives of these great individuals who have changed the century by their works and personal examples. These beautifully written profiles?based on personal interviews with some of these "great souls"?provide the reader with models of excellence that will delight the mind and lift the spirit.
Includes bibliographical references (p. 367-379)
Keywords: GHBiography